ANALYSIS OF WRITTEN MATHEMATICAL COMMUNICATION SKILLS VIA PROBLEM BASED LEARNING IN STORY PROBLEMS - Khoiriyah, Makrifatul; Cholily, Yus Mochamad; Rosyadi, Alfiani Athma Putri; In’am, Akhsanul (Jurnal Muara Pendidikan, 2025)
Mathematical communication skills are crucial for mathematics learning, especially in understanding and solving word problems, which require conceptual understanding and systematic delivery of ideas. One way to help students acquire these skills is by implementing problem-based learning (PBL) methods, which enable them to be actively involved in the problem-solving and exploration process. This study aims to analyze students' written mathematical communication skills through the application of PBL to solving word problems. Subjects and Methods: The research method used was descriptive qualitative with 8 seventh-grade students as subjects. Data were collected through written tests, observations, and documentation, then analyzed based on three main indicators: concept visualization, use of mathematical symbols, and the ability to write explanations systematically. Results: According to the study, students were generally in the high category in written mathematical communication, with an average score of 78, but there were differences among students: four students were in the high category (83-100), one student in the medium category (75), and three students in the low category (58-67). Students in the high category were able to write solutions coherently and clearly, while students in the low category still had difficulty constructing mathematical arguments. PBL can help students in written mathematical communication, especially in understanding and solving story problems.